Clinical Experience in the Management of a Series of Fetal–Neonatal Ovarian Cysts - Constantin-Cristian Văduva; Laurentiu Dira; Dominic Iliescu; Dan Ruican; Anișoara-Mirela Siminel; George Alin Stoica; Mircea-Sebastian Şerbănescu; Andreea Carp-Velișcu (Children, 2025)
Introduction: Fetal ovarian cysts are known to be a common form of fetal abdominal masses in female fetuses, often resulting from hormonal stimulation in utero. Although many resolve spontaneously without sequelae, others can develop into more complex pathologies, such as intracystic hemorrhage or torsion, which can compromise ovarian integrity and long-term reproductive outcomes. Early detection and appropriate follow-up evaluation are therefore crucial for optimal perinatal management. Materials and Methods: We conducted a retrospective study of 12 cases of fetal ovarian cysts diagnosed by routine prenatal ultrasound examinations over a two-year period at our institution. Inclusion criteria were the presence of a cystic adnexal lesion detected in utero, detailed prenatal ultrasound documentation, and a comprehensive postnatal examination. Sonographic features such as cyst size, internal echogenicity, and signs of vascular compromise were recorded. The mother’s clinical variables, including gestational age at diagnosis and relevant medical conditions, were noted. Postnatal follow-up evaluation consisted of ultrasound examinations and, if indicated, pediatric surgical consultation. Results: Of the 12 cases, 9 were characterized by a simple cystic morphology. All spontaneously regressed postnatally and did not require surgical intervention. Three were defined as complex cysts showing septations or echogenic deposits; one of these cysts required immediate surgical exploration for suspected torsion. No cases with a malignant background were identified. All infants showed a favorable course with normal growth and development until follow-up evaluation. Conclusions: This series emphasizes that most fetal ovarian cysts are benign and often resolve without intervention, highlighting the benefit of systematic prenatal imaging. Nevertheless, complex or large cysts require close prenatal and neonatal monitoring to diagnose complications such as torsion.